Pelatihan Smart Diagram Venn Pada Materi Himpunan SMP - Murniasih, Tatik Retno; Ferdiani, Rosita Dwi (Universitas Muhammadiyah Surabaya, 2018)
The purpose of this dedication is to overcome the problems at SMP Al Inayah and Islamic Junior High School PGRI Tutur. The problem in both schools is the lack of learning media in the form of props or other innovative media. Students learn math more through direct explanation by teachers who are dominated by giving lectures. Considering the students' lack of understanding in the set matter it is necessary to hold a manipulative media training activity at SMP Al Inayah Purwosari and Islamic Junior High School PGRI Tutur on the set material. Students in this area desperately need a refresher related to instructional design, in order to develop their conceptual comprehension skills which leads to improving students' mathematics learning outcomes on the subject matter using Venn Smart Diagram media. Benefits of this devotion is the benefits gained among students obtaining learning with manipulative media that are rarely implemented so that students' understanding of the material set increases. Increased understanding of concepts and student learning outcomes in the set material that is marked with 90% of junior high school students Al Inayah and 88% of students of Islamic Junior High School PGRI Tutur can solve the problem set well.Â Â